KAMPUNG VERTIKAL SEBAGAI STRATEGI URBAN RENEWAL DI KAMPUNG LUMUMBA, SURABAYA - Annisa Nur Ramadhani (NALARs, 2021)
Kampung is a settlement that have unique characteristic both in physical and socio-cultural condition. Kampung development process tends to be natural and non-formal, but mainly have faced the environmental degradation and lack of facilities. This forced the government to have some intervention in developing kampung housing by perform an urban renewal. Due to the problem of scarcity of land, urban renewal strategy of kampung has to be developed vertically. This also consider the social context that the rearrangement of kampung area is not done by relocating the local residents, but rearranging the original area to improve the community through environmental, social and economic quality improvement.